2001
DOI: 10.1111/j.1477-8947.2001.tb00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Wider roads, more cars

Abstract: The transport policy currently followed in many European cities seems to be a combination of investments in public transport in order to increase, or at least maintain, its market share, and road building in order to keep up with expected traffic growth. Apparently, there is a prevalent belief among policy makers that increased road capacity in urban areas does not in itself cause any growth in car traffic worth mentioning. Such a belief neglects the simple economic theory of supply and demand, as well as more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…exogenously given total future amounts of traffic, where the traffic in the analysed alternatives differ only in their distribution between different parts of the road network) were used in spite of the fact that the same analyses showed a breakdown of traffic flows on large proportions of the road network in a decade or two if the road capacity was not increased. However, if congestion really grew that bad, many peak-period motorists would choose to go by public transport, bicycle or foot instead of driving (Mogridge, 1997;Naess et al, 2001;Cairns et al, 2002;Noland and Lem, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…exogenously given total future amounts of traffic, where the traffic in the analysed alternatives differ only in their distribution between different parts of the road network) were used in spite of the fact that the same analyses showed a breakdown of traffic flows on large proportions of the road network in a decade or two if the road capacity was not increased. However, if congestion really grew that bad, many peak-period motorists would choose to go by public transport, bicycle or foot instead of driving (Mogridge, 1997;Naess et al, 2001;Cairns et al, 2002;Noland and Lem, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…According to the Downs-Thomson paradox (Downs, 1962;Thomson, 1977) in the long run this can make things worse for both automobile and public transport. According to Mogridge (1990), increased road capacity in congested areas will in the long run only increase flow, not speed, and thus be counter-productive (see also the discussion by Naess et al, 2001). When new roads initially mean less congestion, the automobile will certainly gain popularity and some former passengers of public transit will switch to the private alternative.…”
Section: Mode Of Transport: Increased Share Private Motoring and Trucmentioning
confidence: 95%
“…Today it is an acknowledged fact among most of the researchers in the field that new or improved connections in the transport system generate new traffic (e.g. SACTRA, 1994;Goodwin, 1996;Naess et al, 2001;Noland and Lem, 2002). There is, however, no thorough view of how large these effects are in each individual case.…”
Section: Four Indirect Effects Of Infrastructure Investmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Among suburbanites, there is still a tendency of higher use of public transport among those who live in areas with a high level of public transport accessibility (Naess, Røe & Larsen, ibid. ;Naess, Mogridge & Sandberg, 2001;Hartoft-Nielsen, 2001a). Some influence of proximity to local centers or local service facilities on travel behavior has also been found in some studies, but in the Nordic countries this influence has generally been found to be considerably weaker than that of distance to the main city center (e.g.…”
Section: Residential Location 'State-of-the-art' Knowledgementioning
confidence: 99%